Observing soil organic carbon spatial and seasonal variability at the Golan Heights using CO2/O2 fluxes measurements in an incubation experiment - Tal Weiner; Yoav Rosenberg Oved; Alon Angert (PANGAEA, 2025)
Soil organic matter (SOM) stores most of the terrestrial carbon, and changes in this storage can have a significant effect on the global carbon cycle. Various approaches have been used to understand the SOM transformations and stability. Here we measured the respiratory CO2 and O2 fluxes, and their ratio (the Apparent Respiratory Quotient - ARQ) in soil incubations at different temperatures, to learn about the short-term processes affecting SOM stability. To study in detail the spatial and temporal variability, we examine soil samples from two sample sets: a regional set, and a local set that was used to study the seasonality and environmental variability within a site. The regional set was taken from 11 sites located in the north and center of the Golan Heights, the samplings took place in two campaigns in October 2020 and in January 2021. In each site, the sample was pooled from 2 sub-samples taken by a trowel from A-horizon at 0-10 cm depth in adjacent locations. The local soil samples set was taken from Mt. Baron, a volcanic cinder cone which is located in the north of Golan Heights. The sampling took place in October 2021, February 2022, and June 2022, which represent the beginning, middle, and end of the rainy season. Each sample was pooled from 2 locations and taken by a trowel from A-horizon at 0-10 cm depth. At each campaign, the soil was sampled at 4 heights along the north and south slopes, under tree canopy, and in open grassland. The incubations were conducted on fresh sieved soil (2mm), wetted with distilled water to different levels. To explore the effect of anaerobic microsites on ARQ we incubated artificial clods (1 cm diameter) with wetted soil from Mt. Baron (The local set). To further test the effects of O2 limitation we conducted an experiment in which we mitigated this limitation by enriching in oxygen the atmosphere of the incubation headspace. All the incubations were carried out at the Hebrew University of Jerusalem.